2004
DOI: 10.1128/aem.70.9.5698-5700.2004
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Population Structure of Human Commensal Escherichia coli Isolates

Abstract: The study of several Escherichia coli intestinal commensal isolates per individual in 265 healthy human subjects belonging to seven populations distributed worldwide showed that the E. coli population is highly structured, with major differences between the tropical and temperate populations.Escherichia coli is a commensal inhabitant of the intestinal tracts of healthy humans and many animal species, but it can also cause a wide range of diseases, ranging from diarrhea to extraintestinal infections (8). As it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
191
6
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(226 citation statements)
references
References 21 publications
24
191
6
5
Order By: Relevance
“…Gender distribution of phylogroups showed insignificant differences between females and males. Similar results were obtained by others [25,26] who found that sex and age factors had no effect on distribution of phylogroups. Whereas Gordon et al [27] found that in males the probability of isolating A or D strains increased with host age, whilst the probability of detecting a group B2 strain declined, while in females the probability of recovering A or B2 strains increased with increasing host age and there was a concomitant decline in the likelihood of isolating B1 or D strains.…”
Section: Discussionsupporting
confidence: 79%
“…Gender distribution of phylogroups showed insignificant differences between females and males. Similar results were obtained by others [25,26] who found that sex and age factors had no effect on distribution of phylogroups. Whereas Gordon et al [27] found that in males the probability of isolating A or D strains increased with host age, whilst the probability of detecting a group B2 strain declined, while in females the probability of recovering A or B2 strains increased with increasing host age and there was a concomitant decline in the likelihood of isolating B1 or D strains.…”
Section: Discussionsupporting
confidence: 79%
“…Besides this, assignment of the subgroups (A 0 , A 1 , B1, B2 2 , B2 3 , D 1 and D 2 ) in triplex PCR was evaluated according to Escobar-Paramo et al (2004b).…”
Section: Interpreting Of Results For Phylo-groupingmentioning
confidence: 99%
“…coli is primarily a commensal inhabitant of the mammalian colon, colonizing the gut early after birth and remaining resident throughout the life of the host, but commensal strains differ in their colonization efficiency. E. coli strains belonging to phylogenetic group B2 seem to have a superior capacity to colonize and persist in the colonic microbiota (3), and during the last decade the incidence of B2 strains has risen quickly in colonic microflora of human beings living in high-income countries (2). Surveys have shown that the pks island is present in up to 34% of commensal isolates of phylogenetic group B2 from healthy individuals (4)(5)(6).…”
Section: Discussionmentioning
confidence: 99%